The performance of bioinspired valveless piezoelectric micropump with respect to viscosity change. (29th April 2016) - Lee, Seung Chul; Hur, Sunghoon; Kang, Dooho; Kim, Bo Heum; Lee, Sang Joon
Abstract: This study investigated the effect of the serial connection of two pumping chambers on transport of liquid with increased viscosity. A serially connected valveless piezoelectric micropump was fabricated inspired by the liquid-feeding strategy of a female mosquito drinking liquid with a wide range of viscosities, from nectar to blood. The performance of the micropump was investigated by varying the viscosity of working liquid. Results showed that the optimal phase difference between the two chambers was 180° out-of-phase for all viscosity conditions. The two chambers operating at 180° out-of-phase exhibited higher pumping performance compared with the sum of each single chamber solely actuated, when viscosity increased. The flow patterns in the micropump showed that the rectification efficiency improved with the increase in viscosity. Results indicated that the serially connected valveless piezoelectric micropump is more robust to the increase of viscosity than a single-chamber piezoelectric micropump. This study would be helpful in the design of microfluidic devices for transporting liquids with a wide range of viscosities.